(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2026)
The destructive 1988 Spitak earthquake is one of the most multilaterally and detailedly studied earthquakes in the world. It had severe consequences, and the international community provided unprecedented humanitarian aid to the victims. Numerous scientific papers have been published about this earthquake based on the obtained factual data and the results of their analysis. All this played a significant role in the development of applied seismology and seismic protection. The main objective is to identify the most significant accumulated factual data and the results of their analysis for modern science, to establish their role in the development of science and to indicate promising scientific tasks. The research methodology is based on the assessment of the importance of factual data, the results of their analysis, the value of the problems solved and the determination of their prospects. Results of the work: an attempt was made to determine role of the 1988 Spitak earthquake in the development of applied seismology and seismic protection; for the first time, the most important factual data are grouped; the important tasks that were solved on their basis are indicated; 7 promising scientific tasks are presented; the main literary sources of groups of factual data and the tasks solved on their basis are indicated; a number of factual data are presented that are little known for various reasons to a wide range of specialists.